Analyzing Misconceptions of Acid-Base Topic among Chemistry Education Students in Online Learning Settings: A Case Study - Catur Fathonah Djarwo; Frans Pither Kafiar (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This study aims to identify the misconceptions of 11 third semester Chemistry Education students at Cenderawasih University in relation to online learning during the Covid-19 pandemic. Online learning poses various challenges for both students and lecturers, resulting in incomplete explanations and hindering students' understanding of the material, leading to possible misconceptions. A descriptive qualitative method was employed, utilizing diagnostic tests with a Certainty or Response Index (CRI) and interviews. The findings revealed that 41% of the students had a clear understanding of the acid-base concepts, 30% lacked understanding, and 29% had misconceptions. The students' misconceptions related to six subconcepts in acid-base materials, including acid-base theory, acid-base indicators, acid strength (pH), weak acid-base equilibrium constant (Ka/Kb), calculation of solution pH, and the concept of pH in the environment, with a range of misconceptions from 9-45%. This study highlights the need for addressing misconceptions in online learning, specifically in the acid-base topic, to ensure effective understanding and learning outcomes for students.